Roles for Golgi Glycans in Oogenesis and Spermatogenesis - Akintayo, Ayodele; Stanley, Pamela (Frontiers in Cell and Developmental Biology, 2019)
Glycosylation of proteins by N- and O-glycans or glycosaminoglycans (GAGs) mostly begins in the endoplasmic reticulum and is further orchestrated in the Golgi compartment via the action of >100 glycosyltransferases that reside in this complex organelle. The synthesis of glycolipids occurs in the Golgi, also by resident glycosyltransferases. A defect in the glycosylation machinery may impair the functions of glycoproteins and other glycosylated molecules, and lead to a congenital disorder of glycosylation (CDG). Spermatogenesis in the male and oogenesis in the female are tightly regulated differentiation events leading to the production of functional gametes. Insights into roles for glycans in gamete production have been obtained from mutant mice following deletion or inactivation of genes that encode a glycosylation activity. In this review, we will summarize the effects of altering the synthesis of N-glycans, O-glycans, proteoglycans, glycophosphatidylinositol (GPI) anchored proteins, and glycolipids during gametogenesis in the mouse. Glycosylation genes whose deletion causes embryonic lethality have been investigated following conditional deletion using various Cre recombinase transgenes with a cell-type specific promoter. The potential effects of mutations in corresponding glycosylation genes of humans will be discussed in relation to consequences to fertility and potential for use in contraception.